PENDIDIKAN KARAKTER DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK DI SMP NEGERI 7 DEPOK - Ismail Akbar Brahma (CV. Adiba Aisha Amira, 2024)
Character education is crucial in producing students who are not only academically successful but also ethically and morally sound. Through character education, the role of teachers in schools becomes significantly influential in fostering students' discipline. The continued issues such as tardiness, use of inappropriate language, and not adhering to the uniform policy indicate that student discipline needs improvement. Based on these issues, the research questions are: 1) How is character education implemented at SMPN 7 to achieve student discipline? 2) What efforts are made by the school to instill character education in order to enhance student discipline? This research employs a qualitative descriptive method. The subjects of this study are students at SMP Negeri 7 Depok, and the focus is on the instillation of character in student discipline. This study examines how the embedding of character values contributes to the level of student discipline. Qualitative research involves gathering verbal data and observing behaviors, aiming to create descriptive analyses. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. At SMPN 7 Depok, character education is integrated into every subject. Additionally, the school conducts extracurricular activities such as Friday morning studies, communal cleaning of the school environment, and seminars to socialize character education to students. Teachers must continue to serve as role models and examples for students to enhance discipline, as understanding character education is key to developing disciplined attitudes in students. Both teachers and parents should maintain good communication to monitor and control student behavior at school.